PERAN PESANTREN DALAM MENGHADAPI TANTANGAN DIGITALISASI PENDIDIKAN ISLAM STUDI KASUS MADRASAH TSANAWIYAH PONDOK PESANTREN HIDAYATUL MAARIFIYAH PANGKALAN KERINCI PELALAWAN - Saidah; Sudur; Farida; Asrulla (STKIP Subang, 2026)
This study examines the role of pesantren in managing Islamic Education in the digital era at Madrasah Tsanawiyah Pesantren Hidayatul Maarifiyah Pangkalan Kerinci. A qualitative case study approach was employed, with data collected through interviews, observations, and documentation, and analyzed thematically. The results show that pesantren play a dual role as preservers of traditional values and facilitators of digital adaptation, through the development of interactive materials, digital literacy, and character building. Challenges such as limited facilities, teacher competence, and maintaining pesantren values were addressed through blended learning and teacher training, enhancing motivation, learning effectiveness, independence, and digital ethics among students.